Crescimento e produtividade de cártamo em função da profundidade de semeadura e pressão da roda compactadora - Rosseto, Ricielly Eloyze (2019)
The current search for the development and feasibility of new renewable and environmentally sustainable energy alternatives, such as the so-called "energy crops", provide the energy generation through the oil of their seeds. Safflower, recently introduced in Brazil, attracts this view to its properties and capabilities that can be used in the manufacture of biofuels such as in the food industry. In order to contribute to studies for the viability of this crop in the country, which are still lacking in the management of sowing, the objective of this study was to evaluate the mechanization of sowing of a safflower genotype of two sowing depths (4.5 and 6.5 cm) and three loads on press wheel sowing (117.7, 156.9 and 196.1N) in crop growth and productivity during the pre/ post emergence, flowering and harvest stages around Toledo-PR. The original experimental design was a 2 × 3 factorial data block with four replicates. Seed depths and impact pressures on the compacting wheel did not affect the emergence of safflower seedlings. Root length, plant height, stem diameter and plant dry mass at 30 DAE were benefited with a depth of 4.5 cm in relation to the depth of 6.5 cm. Safflower yield was higher in the 4.5 cm showing depth, while in relation to the pressure factor of the compactor wheel, higher grain yield was observed at a pressure of 196.1 N.